Exposure to inflammatory cytokines IL-1β and TNFα induces compromise and death of astrocytes; implications for chronic neuroinflammation. - Christa van Kralingen (Public Library of Science (PLoS), 2013)
Background Astrocytes have critical roles in the human CNS in health and disease. They provide trophic support to neurons and are innate-immune cells with keys roles during states-of-inflammation. In addition, they have integral functions associated with maintaining the integrity of the blood-brain barrier. Methods We have used cytometric bead arrays and xCELLigence technology to monitor the to monitor the inflammatory response profiles and astrocyte compromise in real-time under various inflammatory conditions. Responses were compared to a variety of inflammatory cytokines known to be released in the CNS during neuroinflammation. Astrocyte compromise measured by xCELLigence was confirmed using ATP measurements, cleaved caspase 3 expression, assessment of nuclear morphology and cell death. Results Inflammatory activation (IL-1β or TNFα) of astrocytes results in the transient production of key inflammatory mediators including IL-6, cell surface adhesion molecules, and various leukocyte chemoattractants. Following this phase, the NT2-astrocytes progressively become compromised, which is indicated by a loss of adhesion, appearance of apoptotic nuclei and reduction in ATP levels, followed by DEATH. The earliest signs of astrocyte compromise were observed between 24-48 h post cytokine treatment. However, significant cell loss was not observed until at least 72 h, where there was also an increase in the expression of cleaved-caspase 3. By 96 hours approximately 50% of the astrocytes were dead, with many of the remaining showing signs of compromise too. Numerous other inflammatory factors were tested, however these effects were only observed with IL-1β or TNFα treatment. Conclusions Here we reveal direct sensitivity to mediators of the inflammatory milieu. We highlight the power of xCELLigence technology for revealing the early progressive compromise of the astrocytes, which occurs 24-48 hours prior to substantive cell loss. Death induced by IL-1β or TNFα is relevant clinically as these two cytokines are produced by various peripheral tissues and by resident brain cells.